Can allergy affect the course of Lyme disease? A case report - Małgorzata A. Czarny-Działak; Jarosław Chmielewski; Martyna Głuszek-Osuch; Anna Słuszniak (Studia Medyczne, 2017)
Sometimes other illnesses can complicate the course of allergic rhinitis, making it difficult to recognise or treat. An example of this type of connection is described in our case report of a patient with allergic rhinitis and concomitant Lyme disease. Aim of the study was to present the case of 54-year-old woman with a severe form of chronic allergic rhinitis, given the diagnosis of Lyme disease coexisting with inflammation of multiple joints. A 54-year-old patient with severe chronic allergic rhinitis, given the diagnosis of Lyme disease. Based on our description of the case, it appears that allergic inflammation from immunity in which a number of cytokines have been activated could be a factor favourable for launch by the spirochete Borrelia burgdorferi arthritis. Maybe the same immune disorders have led to the development of allergies contributing to such a course of Lyme disease and arthritis development.